2015
DOI: 10.1136/bmjopen-2015-008861
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine for the treatment of chronic stable angina: a cost-effectiveness analysis from the UK perspective

Abstract: ObjectivesTo estimate the cost-effectiveness of ranolazine when added to standard-of-care (SoC) antianginals compared with SoC alone in patients with stable coronary disease experiencing ≥3 attacks/week.SettingAn economic model utilising a UK health system perspective, a 1-month cycle-length and a 1-year time horizon.ParticipantsPatients with stable coronary disease experiencing ≥3 attacks/week starting in 1 of 4 angina frequency health states based on Seattle Angina Questionnaire Angina Frequency (SAQAF) scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…A literatura aponta para uma diversidade de tratamentos para a sintomatologia da DTM, são eles: alongamentos e fortalecimento muscular, correção postural, estimulação elétrica nervosa transcutânea (TENS), fisioterapia, terapia de liberação posicional (TLP), crioterapia, laserterapia, técnicas de terapia manual, cinesioterapia, técnicas de relaxamento, facilitação neuromuscular proprioceptiva (FNP) (SOBRAL et al, 2018AKSU et al, 2019.…”
Section: Manifestações Clínicas Das Disfunções Temporomandibularesunclassified
“…A literatura aponta para uma diversidade de tratamentos para a sintomatologia da DTM, são eles: alongamentos e fortalecimento muscular, correção postural, estimulação elétrica nervosa transcutânea (TENS), fisioterapia, terapia de liberação posicional (TLP), crioterapia, laserterapia, técnicas de terapia manual, cinesioterapia, técnicas de relaxamento, facilitação neuromuscular proprioceptiva (FNP) (SOBRAL et al, 2018AKSU et al, 2019.…”
Section: Manifestações Clínicas Das Disfunções Temporomandibularesunclassified
“…29,30,32,34 Cost-Effectiveness Several studies have analysed the cost-effectiveness of ranolazine. [70][71][72] In a systematic review of the existing evidence, Vellopoulou et al found that ranolazine, when added to a standard of care, appeared to be cost-effective primarily due to its ability to decrease angina-related hospitalisation and marginally improve quality of life. 73…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…Evidence from the United States showed that the mean total cost for managing stable angina was ∼$28,590 per patient ( 3 ). Estimations in the United Kingdom showed that stable angina imposes more than £700,000,000 on the National Health Service (NHS) per year ( 4 ). In Canada, the total cost for treating CSA was $19,209 per patient per year by the end of 2008 ( 5 ).…”
Section: Introductionmentioning
confidence: 99%